From health inequalities to equitable health equality: ethical governance in healthcare empowers equity as social justice - Dine, Charles Biradzem; Dany, Rondeau (Journal of Health Inequalities, 2024)
Global millennium healthcare ambition to attain equitable health equality as a prelude to achieving health for all is challenged by increasing health inequalities. First, diversity in the contemporary world is emerging as the unreckoned determinant of health inequalities, and second, the healthcare intervention modalities to subdue health inequalities amidst diversity and attain equitable health equality are not yet sufficiently articulated to help. Thus, the objective of this research is to illustratively demonstrate an innovative healthcare intervention framework to subdue health inequalities amidst diversity, that is, how ethical governance in healthcare empowers equitable intervention against diversity with the impetus of social justice to minimize health inequalities and attain equitable health equality. This healthcare intervention mechanism informs context-sensitive healthcare efforts to ensure that all the people in need communities and individuals are given equal opportunities to have what it takes to be healthy.